KEMISKINAN DAN PENGARUHNYA TERHADAP KEJAHATAN DALAM PERSPEKTIF TEOLOGIS DAN SOSIOLOGIS - Mahmud Ishak (TAHKIM, 2017)
The poverty is sometimes supposed as a part of Allah destiny and identifies the poverty as the pious lifestyle. The assumption that poverty as part of Allah destiny has been a justification reason the emergence of lazy attitude on the part of Muslims to seek for the sustenance. In addition, the proliferation of many crimes that occurred in various parts of the country at homeland there is relation to the poverty wrapped to the offenders. So that sociologically the poverty is one of the main causes of crime. And theologically, the poverty is considered as the causing root of kufr, because the act of committing crime itself becomes a measurement the fragility of one's faith. Keywords: poverty, crime, theological and sociological perspectives